Analisis Pengaruh Komitmen Organisasi Dan Kepuasan Kerja Terhadap Turnover Intention Karyawan Dealer Honda CV. Semoga Jaya Cabang Tenggarong - Mawardi, Mawardi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2016)
This study was the result of the development of the research model based on the result of scientific exploration through literature review and observations on the object of research. A series of observations carried out on the object of research which is dealer companies CV. Semoga Jaya Branch Tenggarong who have employee turnover level, which reached presentations 58.33% in one year period, but the focus that made this research is on the aspect of intention or a tendency of employees to leave the company (turnover intention). To measure the symptoms above data analysis techniques using multiple regression analysis with organizational commitment independent variable(X1) and job satisfaction (X2). The results of such research is not discover the simultan relationships among variables with the calculated F value 0.058 and the value of F table 3,23. The next hypothesis is to identify the relationship partially through t test obtained the same results with no evidence of the hypothesis that by obtaining t value of 0.186 for the variable of organizational commitment (X1), and job satisfaction (X2) of -340. Then to regression equation generated through this research is Y = 3.378 + 0,028X1 - 0,076X2Keywords: Job Satisfaction, Organizational Commitment, turnover intention